Pemanfaatan Website Desa Dalam Optimalisasi Informasi Publik kepada masyarakat di Desa Kiringan - Pamungkas, Ridho; Saifullah, Saifullah; Pratama, Qoirrudin Raga; Try Cahyo, Okky Aldhy (JURNAL DAYA-MAS, 2020)
Abstract— Information and communication technology is currently developing very rapidly, this is indicated by the use of the internet by the general public. The internet as a medium of communication and information has now become a primary need. The benefits of the internet are very large, especially in the world of education, entertainment, business and government. Kiringan village is one of the villages located in Takeran District, Magetan Regency. Kiringan Village still uses conventional information media, namely by using a notice board located at the village office to convey public information such as an introduction to the organizational structure, activities, location and village potentials that the community feels is less legible. With the development of information and communication technology that is increasingly rapid and massive, the village of Kiringan needs an online information medium which can also be called a village website. So that this village website is expected to optimize public information to the Kiringan village community and the community outside the Kiringan village as a village promotion media in introducing the village potentials as well as the administration of public services in the Kiringan village. Keywords—: Information Technology; Kiringan Village; Public service; Village Website.